Efektivitas Uji Latihan Kardio-Pulmoner (CPET) dan Uji Jalan Kaki Enam Menit (6MWT) pada Pasien Pasca-CABG - Ekawati, Shintia; Dewi, Yulis Setiya; Wahyuni, Erna Dwi; Kristiningrum, Sifira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to evaluate the effectiveness of Cardiopulmonary Exercise Testing (CPET) and Six-Minute Walking Test (6MWT) in the rehabilitation management of patients after Coronary Artery Bypass Graft (CABG) surgery. Methods included a systematic review of 15 relevant studies, with data analysed using an integrative approach. Results showed that CPET provides in-depth information on cardiorespiratory responses during exercise, while 6MWT provides an evaluation of the patient's functional capacity. Both tests play an important role in personalised rehabilitation planning to improve patients' exercise capacity and quality of life. The conclusion of this review confirms the importance of the combined use of CPET and 6MWT to maximise rehabilitation outcomes of post-CABG patients. Keywords: coronary artery bypass, exercise test, cardiac rehabilitation, walking test, cardiovascular surgical procedure